(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research explores the psychosocial characteristics and examines the supporting and inhibiting factors affecting high-achieving soccer athletes in Jambi Province, Indonesia. A qualitative case study approach was employed with six high-achieving soccer athletes who demonstrated excellence at provincial and district levels through the Governor’s Cup and regional competitions. Data collection utilized in-depth interviews, direct observation, and documentation, followed by data reduction, presentation, and conclusion verification analysis. The findings reveal that psychosocial conditions among high-achieving soccer athletes in Jambi Province are shaped by the interplay between psychological and social dimensions. Psychologically, athletes demonstrate capabilities in emotional regulation, stress management, and trauma recovery, supported by intrinsic motivation and aspirations for professional careers. Socially, athletes exhibit strong adaptability, maintain positive team relationships, and actively participate in community activities. Supporting factors encompass internal motivation, family support, and tournament participation. Conversely, inhibiting factors include mental pressure, injury-related trauma, facility limitations, and insufficient governmental support alongside economic constraints. These findings emphasize the necessity for comprehensive psychosocial support systems in athlete development programs to optimise performance and mental well-being. This study includes 6 in-depth interviews, observational data, and documentation from various soccer tournaments and training sessions.